3D Multi-Domain MFS Analysis of Sound Pressure Level Reduction Between Connected Enclosures - Luıs GODINHO; Fernando G. BRANCO; Paulo AMADO MENDES (Archives of Acoustics, 2013)
In this paper, the authors study the 3D propagation of sound waves between two closed spaces. The separation element between the two rooms is considered to include either a small opening or a homogeneous lightweight panel, coupling the two spaces. A numerical study of this configuration is performed, trying to understand the influence of the position and geometry of this opening in the sound pressure level reduction curve at low and midfrequencies. Additionally, the coupling effect between the two acoustic spaces is analyzed, in order to better understand its importance when determining the sound pressure level reduction. Different boundary conditions are ascribed to the walls of these rooms, simulating both the completely reflecting and partially absorbing surfaces. The numerical modelling was performed using a multi-domain formulation of the Method of Fundamental Solutions (MFS). The system is composed of two coupled rooms, limited by rigid or by absorbing walls, and separated by a thin wall (tending to null thickness) with a small opening. An experimental validation of the pro- posed model is presented, comparing its results with those found experimentally for a reduced-scale model. It is important to note that, for such a configuration, a tra- ditional single-domain approach using methods like the MFS or the BEM would lead to undetermined equation systems, and thus the proposed model makes use of a domain decomposition technique.